2014
DOI: 10.1117/1.oe.53.10.107106
|View full text |Cite
|
Sign up to set email alerts
|

Metal-semiconductor-metal ultraviolet photodetectors based on gallium nitride grown by atomic layer deposition at low temperatures

Abstract: Abstract. Proof-of-concept, first metal-semiconductor-metal ultraviolet photodetectors based on nanocrystalline gallium nitride (GaN) layers grown by low-temperature hollow-cathode plasma-assisted atomic layer deposition are demonstrated. Electrical and optical characteristics of the fabricated devices are investigated. Dark current values as low as 14 pA at a 30 V reverse bias are obtained. Fabricated devices exhibit a 15× UV/VIS rejection ratio based on photoresponsivity values at 200 nm (UV) and 390 nm (VIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…He et al [ 22 ] directly deposited the PEALD GaN thin films, with an oxygen content of 11.61 at.%, on multilayer graphene in order to improve the performance of GaN-based optical and high-power devices. Tekcan et al [ 44 ] prepared PEALD GaN films at 200 °C and demonstrated the viability of PEALD GaN-based ultraviolet photodetectors with temperature-sensitive substrates used in flexible and transparent optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…He et al [ 22 ] directly deposited the PEALD GaN thin films, with an oxygen content of 11.61 at.%, on multilayer graphene in order to improve the performance of GaN-based optical and high-power devices. Tekcan et al [ 44 ] prepared PEALD GaN films at 200 °C and demonstrated the viability of PEALD GaN-based ultraviolet photodetectors with temperature-sensitive substrates used in flexible and transparent optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…GaN (PE-ALD) [1,8,10,11,13,14,16,20,21,30,35] GaN devices (PE-ALD) [2,4,10,11,17] Nanofibers (PE-ALD) [5,[9][10][11]] Nanostructures (ALD) [18,21] AlGaN (PE-ALD) [1,3] AlN (PE-ALD) [1,5,[19][20][21]29,32] BN (PE-ALD) [5,6,11] InN (PE-ALD) [10,11,15,[19][20][21]33,34] BInN and BGaN (PE-ALD)…”
Section: Materials (And Process) Referencementioning
confidence: 99%
“…As a matter of fact, the number of ALD GaN reports, focussed mostly on the material properties, is growing in the recent times 53,[89][90][91][92][93][94][95][96] . Some of the reported (and perceived) applications include TFTs [43][44] , sensors, and photodetectors [97][98][99] .…”
Section: Introductionmentioning
confidence: 99%